2022
DOI: 10.1186/s41938-022-00553-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of indigenous Bacillus thuringiensis isolate RM11 toxic to the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae)

Abstract: Background Bacillus thuringiensis (Bt) Berliner is an omnipresent soil bacterium used as world’s leading biopesticide to combat agriculturally important insect pests. This study was aimed at protein and gene profiling of an indigenous Bt isolate RM11, which was toxic to the larvae of diamondback moth, Plutella xylostella (L.) in laboratory bioassays. Results Indigenous Bt isolate RM11 was characterized along with the standard checks B. thuringiensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Manikandan et al [26] observed the occurrence of bipyramidal and cuboidal shapes of inclusions in Bt isolate T30 whereas isolate T48 contains only bipyramidal shaped inclusions. While, Navya et al [32] observed that Bt isolate RM11 effective against Plutella xylostella was found to possess three different shapes of crystals such as bipyramidal, spherical and cuboidal. These results suggested that the Bt isolates toxic to lepidopteran insects were found to have bipyramidal and cuboidal shape of crystal inclusions.…”
Section: Colony and Crystal Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Manikandan et al [26] observed the occurrence of bipyramidal and cuboidal shapes of inclusions in Bt isolate T30 whereas isolate T48 contains only bipyramidal shaped inclusions. While, Navya et al [32] observed that Bt isolate RM11 effective against Plutella xylostella was found to possess three different shapes of crystals such as bipyramidal, spherical and cuboidal. These results suggested that the Bt isolates toxic to lepidopteran insects were found to have bipyramidal and cuboidal shape of crystal inclusions.…”
Section: Colony and Crystal Morphologymentioning
confidence: 99%
“…Maheesha et al[31] recorded LC 50 value of 2.04 µg/ml in an indigenous Bt isolate against S. frugiperda. Similarly, Bt isolate RM11 expressed the toxicity on Plutella xylostella with 4.51 µg/ml[32]. Lone et al[41] reported two isolates, JK12 and JK17 with LC 50 value of 184.62 and 275.39 µg/ml against Helicoverpa armigera.…”
mentioning
confidence: 98%
“…Bacteria are unicellular prokaryotes with distinctive physiological, morphological, and evolutionary attributes. , They could be used to combat pests and phytopathogens. Bacteria used as BCAs or BBCAs belong to four major categories, , namely, crystalliferous spore formers, , obligate pathogens, , potential pathogens, , and facultative pathogens. BBCAs are a widely utilized microbial biological control (MBCA) that works in various ways for the eradication of pests. The two significant prerequisites to achieving efficacy are interaction and ingestion by the potential pests.…”
Section: Bacteria-derived Nanobiopesticides (B-nbps) As Plant Protect...mentioning
confidence: 99%